A modified Fault Diagnosis Scheme in Wireless Sensor Net-works - Mothe, Rajesh; Balija, Swathi; Chanti, Yerrolla; Kumar, Bura Vijay (International Journal of Engineering and Technology, 2018)
The sensor nodes in wireless sensor networks may be deployed in unattended and possibly hostile environments. In addition, node failures and environmental hazards cause frequent topology changes, communication failures, and network partitioning. This in turn adds a new dimension to the fragility of the network topology. In this paper we propose the modified distributed algorithm that could notice the defective nodes existing pool system and upon detection removes those in order to safeguard the faulty data may arrive the wireless network. The algorithm works with twofold former one is to check for the node observations and related with them previous observations to make sure for consistency of data and later is to publish to the neighboring nodes to know the status of the error and eliminates completely from the network.